Chionea Dalman newly recorded from China with descriptions of two new species (Diptera, Limoniidae) - Zhang, Xiao; Wang, Junchao; Yang, Ding (Zootaxa, 2012)
The genus Chionea Dalman, 1816 is recorded from China for the first time with the following four species belonging tothe subgenus Chionea s. str.: Chionea (Chionea) crassipes gracilistyla Alexander, 1936, C. (C.) pusilla Savchenko, 1983,C. (C.) sphaerae sp. nov. and C. (C.) tianhuashana sp. nov.. A key to the known species of Chionea from Eastern Palaearctic is presented.